Diversity and Localization of Bacterial Endosymbionts from Whitefly Species Collected in Brazil - Marubayashi, Julio Massaharu [UNESP]; Kliot, Adi; Yuki, Valdir Atsushi; Marques Rezende, Jorge Alberto; Krause-Sakate, Renate [UNESP]; Pavan, Marcelo Agenor [UNESP]; Ghanim, Murad (Public Library Science, 2014)
Whiteflies (Hemiptera: Aleyrodidae) are sap-sucking insect pests, and some cause serious damage in agricultural crops by direct feeding and by transmitting plant viruses. Whiteflies maintain close associations with bacterial endosymbionts that can significantly influence their biology. All whitefly species harbor a primary endosymbiont, and a diverse array of secondary endosymbionts. In this study, we surveyed 34 whitefly populations collected from the states of Sao Paulo, Bahia, Minas Gerais and Parana in Brazil, for species identification and for infection with secondary endosymbionts. Sequencing the mitochondrial Cytochrome Oxidase I gene revealed the existence of five whitefly species: The sweetpotato whitefly Bemisia tabaci B biotype (recently termed Middle East-Asia Minor 1 or MEAM1), the greenhouse whitefly Trialeurodes vaporariorum, B. tabaci A biotype (recently termed New World 2 or NW2) collected only from Euphorbia, the Acacia whitefly Tetraleurodes acaciae and Bemisia tuberculata both were detected only on cassava. Sequencing rRNA genes showed that Hamiltonella and Rickettsia were highly prevalent in all MEAM1 populations, while Cardinium was close to fixation in only three populations. Surprisingly, some MEAM1 individuals and one NW2 population were infected with Fritschea. Arsenopnohus was the only endosymbiont detected in T. vaporariorum. In T. acaciae and B. tuberculata populations collected from cassava, Wolbachia was fixed in B. tuberculata and was highly prevalent in T. acaciae. Interestingly, while B. tuberculata was additionally infected with Arsenophonus, T. acaciae was infected with Cardinium and Fritschea. Fluorescence in situ hybridization analysis on representative individuals showed that Hamiltonella, Arsenopnohus and Fritschea were localized inside the bacteriome, Cardinium and Wolbachia exhibited dual localization patterns inside and outside the bacteriome, and Rickettsia showed strict localization outside the bacteriome. This study is the first survey of whitely populations collected in Brazil, and provides further insights into the complexity of infection with secondary endosymionts in whiteflies.